Application of Decision Support System in Determining the Best Physics Learning Media Aids Using VIKOR, EDAS, and EXPROM II Methods - Yono Cahyono; Perani Rosyani; Resti Amalia; Sewaka; Alfitri Rizka Rinanda; Muhammad Rizki; Okvrilllia Reony Ondri (PT FORMOSA CENDEKIA GLOBAL, 2023)
The development of effective physics learning media is a major challenge in supporting an innovative and result-oriented learning process. This research aims to implement a Decision Support System (DSS) in the selection of physics learning media aids by using the EDAS, VIKOR, and EXPROM II methods. The EDAS method is used to evaluate alternative learning media tools based on tiered preferences, while VIKOR provides an optimal solution by considering the best and worst values. In addition, EXPROM II provides an explicit assessment of complexity and risk in the context of physics learning media selection. The practical implications of these findings can help decision makers in the field of education to improve the quality of physics learning media used in the educational process